Implications of HLA-allele associations for the study of type IV drug hypersensitivity reactions. (4th March 2018) - Sullivan, A.; Watkinson, J.; Waddington, J.; Park, B. K.; Naisbitt, D. J.
ABSTRACT: Introduction : Type IV drug hypersensitivity remains an important clinical problem and an obstacle to the development of new drugs. Several forms of drug hypersensitivity are associated with expression of specific HLA alleles. Furthermore, drug-specific T-lymphocytes have been isolated from patients with reactions. Despite this, controversy remains as to how drugs interact with immune receptors to stimulate a T-cell response. Areas covered : This article reviews the pathways of T-cell activation by drugs and how the ever increasing number of associations between expression of HLA alleles and susceptibility to hypersensitivity is impacting on our research effort to understanding this form of iatrogenic disease. Expert opinion : For a drug to activate a T-cell, a complex is formed between HLA molecules, an HLA binding peptide, the drug and the T-cell receptor. T-cell responses can involve drugs and stable or reactive metabolites bound covalently or non-covalently to any component of this complex. Recent research has linked the HLA associations to the disease through the characterization of drug-specific T-cell responses restricted to specific alleles. However, there is now a need to identify the additional genetic or environment factors that determine susceptibility and use our increased knowledge to develop predictive immunogenicity tests that offer benefit to Pharma developing new drugs.